2020
DOI: 10.1016/j.jviromet.2019.113806
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of preferred codon usage in the coronavirus N genes and their implications for genome evolution and vaccine design

Abstract: The nucleocapsid (N) protein of a coronavirus plays a crucial role in virus assembly and in its RNA transcription. It is important to characterize a virus at the nucleotide level to discover the virus's genomic sequence variations and similarities relative to other viruses that could have an impact on the functions of its genes and proteins. This entails a comprehensive and comparative analysis of the viral genomes of interest for preferred nucleotides, codon bias, nucleotide changes at the 3 rd position (NT3s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 61 publications
3
58
0
Order By: Relevance
“…We calculated the nucleotide compositions of the coronavirus genomes under study (see Table 1). Previous results showed that the gene N, which follows the trend A > U > G > C [12] and the coronavirus RNA genomes are biased towards high AU content and low GC content [31]. In line with that, our results show that the nucleotide A is the most frequent base and the nucleotide composition follows the trend A > U > G > C (see Table 2).…”
Section: Nucleotide Compositionsupporting
confidence: 90%
See 1 more Smart Citation
“…We calculated the nucleotide compositions of the coronavirus genomes under study (see Table 1). Previous results showed that the gene N, which follows the trend A > U > G > C [12] and the coronavirus RNA genomes are biased towards high AU content and low GC content [31]. In line with that, our results show that the nucleotide A is the most frequent base and the nucleotide composition follows the trend A > U > G > C (see Table 2).…”
Section: Nucleotide Compositionsupporting
confidence: 90%
“…The corresponding gene products are involved in essential viral functions. Briefly, S protein regulates viral attachment to the receptor of the target host cell [39]; E protein functions to assemble the virions and acts as an ion channel [40] M protein plays a role in viral assembly and is involved in the biosynthesis of new virus particles [41]; N protein forms the ribonucleoprotein complex with the viral RNA [12]; RdRP catalyzes viral RNA synthesis. For these five proteins the RSCU vectors in each virus of the dataset are shown in Figures 4 and A5.…”
Section: Selective Pressures and Mutational Rates Characterizing Fivementioning
confidence: 99%
“…The nucleotide content of 30 coronaviruses coding sequences are calculated. The results reveal that the nucleotide A is the most frequent base and the nucleotide frequencies are in order A >T>G>C [19]. For nCoV we note a different trend T>A>G>C, but in totally AT% is more used than GC% (See Table 3).…”
Section: Nucleotide Compositionmentioning
confidence: 81%
“…So, only five virall genes are classified according to their viral location and studied for each virus because the short length and insufficient codon usage diversity of the other genes might have biased the results. The corresponding gene products including S protein regulates virus attachment to the receptor of the target host cell [2]; the E protein functions to assemble the virions and acts as an ion channel [18], the M protein plays a role in virus assembly and is involved in biosynthesis of new virus particles [17] the N protein forms the ribonucleoprotein complex with the virus RNA [19]. Finally, RdRP catalyzes viral RNA syntesis.…”
Section: Genesmentioning
confidence: 99%
“…Different organisms, even different protein coding genes of the same species, have different frequency of codon usage (16). The RSCU bias will reveal the difference of the host source.…”
Section: Codon Usage Has Small Impact On the Mutation Pattern Betweenmentioning
confidence: 99%